Improving Knowledge of Balanced Nutrition and Monitoring The Nutritional Status of Toddlers In Mothers at Posyandu in Sei Naga Lawan Village - Panjaitan, Raini; Sitepu, Sari Desi Esta Ulina; Ginting, Joe Chresnando; Cholilluloh, Andreais Boffil; Ginting, Desri Meriahta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Toddler nutrition problems are one of the determinants of the quality of human resources in the future. Toddlers have the potential to be very vulnerable to nutritional problems, which are caused by a lack of nutritional intake. The need for nutrients plays a role in optimizing the growth and development of toddlers. Nutritional problems can be overcome depending on the role of parents, especially mothers. This community service activity aims to increase knowledge about balanced nutrition and monitor the nutritional status of toddlers. The method used in this activity is using education through balanced nutrition counseling and monitoring the nutritional status of toddlers to mothers who have children aged 0 to 60 months by providing leaflets to participants. The number of participants who took part in the activity was 27 people. The implementation of the Community Service activity was carried out by a team of lecturers and students from the Nutrition Study Program INKES Medistra Lubuk Pakam in 2024. This Community Service was also accompanied by cadres of the Nagalawan Village Posyandu and health workers from the Melati Melati Health Center, Serdang Bedagai Regency. From 27 participants, data was obtained that there was an increase in knowledge, proven by mothers who had good knowledge previously as many as 3 people after being given counseling increased to 12 people, which means there was an increase of 33.33%. The results of monitoring the nutritional status of toddlers in Nagalawan Village showed that the nutritional status of toddlers with the category of malnutrition was 7 people (26.0%), the normal nutritional category was 12 people (44.4%). In comparison, the excess nutritional category was 8 people (29.6%). In the PkM activity, it can be concluded that there was an increase in maternal knowledge of 33.33%. The use of leaflet media, lecture methods, and questions and answers effectively increased maternal knowledge in Nagalawan Village. The results of monitoring the nutritional status of toddlers with the majority of toddlers with the normal nutritional category were 12 people (44.4%).